A Novel Quarter‐Circular Arc Multi‐Direction Piezoelectric VEH and Its Theoretical Model. Issue 1 (1st January 2021) - Yucheng, Zhu; Jiayang, Hu; Yunshan, Bai; Jiang, Zhao; Xincun, Ji; Debo, Wang
Abstract : A quarter‐circular arc piezoelectric Vibration energy harvester (VEH) based on nonlinear geometry is proposed with both bending moment and torque deformation mode, so it can effectively absorb multidirectional vibration at the same resonance frequency. The theoretical model of quarter‐circular arc piezoelectric VEH is established to study the resonance frequency and the output voltage. In order to demonstrate multi‐directional performance of the quarter‐circular arc VEH, the stress distribution is compared with that of the traditional piezoelectric VEH in multi‐direction vibration, and the output voltage of the circular arc piezoelectric VEH are relatively increased 267.26% in X‐direction, 463.18% in Y‐direction, and 17.24% in Z‐direction. The external load is equipped in circuit to measure output power, whose matching resistance is around 21kΩ, and the maximum output powers are 7.57mW in X‐direction, 2.39mW in Y‐direction, and 9.93mW in Z‐direction.